Overview of Teacher Ability Using Core Type Cooperative Model with Blended Learning Method to Increase Student Learning Outcomes - Elisa Kasli; Ahmad Farhan; Susanna Susanna; Fitria Herliana; Sri Wahyuni (Jurnal Penelitian Pendidikan IPA, 2022)
The low teaching ability of teachers is one of the factors that cause low student learning outcomes. The purpose of this research is to examine and analyze the ability of teachers to teach and students' learning completeness. This research is classroom action research. Collecting data using student learning outcomes tests and observation sheets of teacher teaching abilities. Analysis of student learning outcomes test data was carried out using percentage statistics, and observational data on teachers' teaching abilities were analyzed using descriptive assessment scores. The results showed that the teacher's ability to manage to learn has increased in each cycle. In cycle 1, it was included in the poor category, then increased in cycle 2 to be good and increased again in cycle 3 to be better. Student learning outcomes increase in each cycle. Individually in cycle 1,.35% complete their learning. Cycle 2 is 60.00% and cycle 3 is 92.00%. Classical completeness in cycle 1 is 42.00%, cycle 2 is 65.00% and cycle 3 is 85.00%.